Pendampingan Santri Dalam Memahami Isim Isyarah Pada Kalimat Bahasa Arab di Kelas 4 Ibtida’iyyah Madrasah Diniyah Assunniyyah Kencong-Jember - Furoidah, Asni; Jum’ah, Masruroh Lailatal (Yayasan Daarul Huda Kruengmane, 2024)
In understanding Arabic, it is very important to master the science of nahwu which is a tool to make it easier to understand the composition of Arabic sentences correctly. There are so many terms in the science of nahwu, one of which is the term isimisyarah which describes a clue to explain something. This isimisyarah material can make it easier to understand the composition of Arabic sentences who think that learning is boring and difficult. The purpose of this community service activity is to assist the 4th grade students of Ibtida'iyyah Madrasah AssunniyyahKencongJember in understanding isimisyarah in Arabic sentences. The method used is with three elements, namely: preparation for implementation and evaluation. The results of this mentoring can be seen from an oral test on the understanding of isimisyarah with an average value of 85, a test of understanding isimisyarah in Arabic sentences with an average value of 90 from students who have carried out the test. It can be concluded that the mentoring carried out for grade 4 ibtida'iyyah students in understanding the isimisyarah in Arabic sentences has been successful and can be continued for a longer period of time.